Cerebral small vessel disease mediates the association between homocysteine and cognitive function - Teng, Zhenjie; Feng, Jing; Liu, Ronghui; Ji, Yifan; Xu, Jing; Jiang, Xin; Chen, Huifang; Dong, Yanhong; Meng, Nan; Xiao, Yining; Xie, Xiaohua; Lv, Peiyuan (Frontiers in Aging Neuroscience, 2022)
Objective: To investigate the relations of serum total homocysteine (tHcy) with cerebral small vessel disease (CSVD) and cognitive function and evaluate whether CSVD mediates the effect of serum tHcy on cognitive function. Methods: A total of 1033 consecutive eligible participants who received serum tHcy, brain magnetic resonance imaging (MRI), and neuropsychological assessment were included in this retrospective study. White matter hyperintensity, lacune, cerebral microbleed and enlarged perivascular space were evaluated based on brain MRI. We used multivariate binary logistic regression analysis, multivariate ordinal logistic regression analysis and mediation analyses to assess the relations of serum tHcy with CSVD and cognitive function. Results: Serum tHcy levels were higher in patients with cognitive impairment than those with no cognitive impairment (median 17.5 vs 13.7 umol/L; P <0.001). Logistic regression analyses showed elevated serum tHcy was associated with cognitive impairment (odds ratio [OR]: 1.037; 95% confidence interval [CI]: 1.021 to 1.053; P <0.001) and higher CSVD burden score (OR: 1.047; 95%CI: 1.034 to 1.061; P <0.001) after adjusting potential confounders. Compared with the lowest tHcy quartile (＜11.81 µmol/L), the multivariable-adjusted OR of the highest quartile (＞19.10 µmol/L) was 4.851 (95% CI: 3.152 to 7.466; P for trend <0.001) for cognitive impairment, 3.862 (95% CI: 2.467 to 6.047; P for trend <0.001) for severe CSVD burden score. Mediation analyses showed significant moderating effects (9.3%-23.6%) by different imaging markers of CSVD on the association between higher serum tHcy levels and cognitive impairment. Conclusions: Elevated serum tHcy is associated with cognitive impairment and the development of CSVD. A proportion of the association between elevated serum tHcy and cognitive impairment may be attributed to the presence of different imaging markers of CSVD, especially the severe CSVD burden score.